2021
DOI: 10.1590/pboci.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Analysis of Streptococcus mutans Growth and Biofilm Formation in Saliva and Histatin-5 Relate to pH and Viscosity

Abstract: Objective: To analyze the ability of saliva in controlling the growth and the biofilm formation of Streptococcus mutans (S. mutans) as well as the effect of histatin-5 anti-biofilm relate to pH and saliva viscosity. Material and Methods: The S. mutans biofilm assayed by crystal violet 1% and its growth measured by spectrophotometer. The saliva viscosity was analyzed by viscometer, and pH of saliva was measured by pH meter. Results: Based on the optical density values, growth of S. mutans in saliva ranged <300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It was then incubated in an aerobic atmosphere at 37 0 C for 24 h. The film residue was separated by centrifuging 3000xg for 10 min, and the supernatant was considered living bacterial cells. Furthermore, it was measured by spectrophotometry with a wavelength of 600 nm [25].…”
Section: -11-antibacterial Assaymentioning
confidence: 99%
“…It was then incubated in an aerobic atmosphere at 37 0 C for 24 h. The film residue was separated by centrifuging 3000xg for 10 min, and the supernatant was considered living bacterial cells. Furthermore, it was measured by spectrophotometry with a wavelength of 600 nm [25].…”
Section: -11-antibacterial Assaymentioning
confidence: 99%
“…In complex oral environment, the formation of dental biofilm was also affected by saliva secreted (De Foggi et al 2018). Syafriza et al (2021) found that saliva inhibited the growth and biofilm formation of S. mutans. Silva et al (2012) reported that artificial saliva could affect the biofilm formation of C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…Syafriza et al . (2021) found that saliva inhibited the growth and biofilm formation of S. mutans . Silva et al .…”
Section: Introductionmentioning
confidence: 99%